Pengaruh Inhalasi Peppermint dengan Mual Muntah Pada Ibu Hamil Trimester I - Hodijah, Hodijah; Febriayanti, Hellen; Sanjaya, Riona (Utan Kayu Publishing, 2021)
Based on the Lampung Province Health Profile in 2017, the high incidence of emesis gravidarum in pregnant women was 50- 90%, while hyperemesis gravidarum reached 10-15% in Lampung Province from the number of pregnant women who were 182,815 people. The research objective was to determine the effect of peppermint inhalation with nausea and vomiting in TM I pregnant women at BPM Hodijah Rejo Mulyo Village, Pasir Sakti District, East Lampung Regency in 2021. This research is quantitative research, with a quasi-experimental research design or quasi-experimental research. The subjects in this study were all pregnant women at BPM Hodijah with the object of TM I pregnant women who experienced nausea and vomiting. The research was conducted in January - February 2021 at PMB Hodijah. The results showed that the average nausea and vomiting before being given peppermint inhalation intervention was 8.90 after being given peppermint inhalation was 6.55 with a standard deviation value of 1.538, a minimum value of 4 and a maximum value of 9. There was an effect of inhalation of peppermint with nausea and vomiting in TM I pregnant women. In BPM Hodijah Rejo Mulyo Village, Pasir Sakti District, East Lampung Regency in 2021 with a P-value of 0,000. Suggestions that can be used as a reference in the learning process in the discussion of pregnant women with nausea and can be used as study material in providing treatment for pregnant women with nausea and vomiting.